High-strength early-strength cement-based composite material and preparation method thereof
By using modified polypropylene fibers and modified nanomaterials in cement matrix composites, a complex network structure is formed, which solves the problems of low strength and poor permeability in the early stage of underwater concrete in the prior art, and a cement matrix composite with high strength, permeability grade and high freeze-thaw resistance are achieved.
Patent Information
- Application Number
- CN202411614955.6
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-13
- Publication Date
- 2025-03-11
- Estimated Expiration
- 2044-11-13
AI Technical Summary
The prior art is difficult to provide high-strength, impermeability grade and high-strength concrete when used underwater, and has low early strength, decreased later strength, complex raw material composition, frequent adjustment of proportions, poor applicability.
A high-strength early-strength cement matrix composite material is adopted, including ordinary silicate cement, silica fume, modified polypropylene fiber, aqueous epoxy resin emulsion, modified nanomaterials, polyamine curing agent, quartz sand, hydroxypropyl methylcellulose, fast hardener, water reducing agent and defoaming agent. By modifying modified polypropylene fiber and nanomaterials, a complex network structure is formed to improve the compressive strength and permeability of concrete.
The 28d compressive strength and permeability of cement matrix composite materials are significantly improved, the flexural tensile strength and freeze-thaw resistance are improved, and the overall load-bearing capacity and durability of concrete are enhanced.
Smart Images

Figure BDA0005131935670000121 
Figure BDA0005131935670000131
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of concrete, and particularly relates to a high-strength early-strength cement-based composite material and a preparation method thereof. Background Art
[0002] Concrete is an artificial stone material widely used in the fields of construction and civil engineering. It is made of cement, fine aggregate (usually sand), coarse aggregate (such as crushed stone or pebbles) and water mixed in a certain proportion. Sometimes some additives such as water reducer, retarder, early strength agent, etc. are added to improve the properties of concrete.
[0003] Concrete is widely used underwater, especially in the fields of marine engineering, water conservancy engineering, bridge construction, etc. When used underwater, concrete needs to have a high early strength to facilitate the implementation of steel grouting; at the same time, it needs a high impermeability grade and high strength to improve the durability of concrete.
[0004] In the prior art, the following methods are generally adopted to improve the early strength of concrete: (1) using silicate cement as the main cementitious material and adding other admixtures and mineral admixtures for modification, but its early strength is low and its volume shrinkage is large in the later period; (2) using sulphoaluminate mineral cement and aluminate mineral cement as cementitious materials, but the production cost is high and the strength in the later period will decrease; (3) compounding silicate cement and sulphoaluminate mineral cement and adding other admixtures for modification, but the raw material composition is complex, the ratio needs to be adjusted frequently, and the applicability is poor. The above methods cannot meet the needs of the existing market.
[0005] Therefore, there is an urgent need for a high-strength, early-strength cement-based composite material and a preparation method thereof. Summary of the invention
[0006] The purpose of the present invention is to provide a high-strength early-strength cement-based composite material and a preparation method thereof.
[0007] In order to achieve the above object, the present invention provides the following technical solutions:
[0008] A high-strength early-strength cement-based composite material, comprising the following components in parts by weight: 400-450 parts of ordinary Portland cement, 20-25 parts of silica fume, 7-12 parts of modified polypropylene fiber, 80-90 parts of waterborne epoxy resin emulsion, 1-3 parts of modified nanomaterials, 10-12 parts of polyamine curing agent, 530-580 parts of quartz sand, 5-12 parts of hydroxypropyl methylcellulose, 60-80 parts of quick-hardening agent, 4-7 parts of water reducing agent and 1-3 parts of defoaming agent;
[0009] The preparation method of modified polypropylene fiber comprises the following steps:
[0010] (1) 90 parts by weight of polypropylene, 5-7 parts by weight of titanium dioxide, and 4-6 parts by weight of 3-isocyanatepropyltrimethoxysilane (CAS: 15396-00-6) are uniformly mixed, and the mixture is mixed and extruded into granules by a twin-screw extruder at an extrusion temperature of 180-185° C. to obtain a modified polypropylene masterbatch;
[0011] (2) The modified polypropylene masterbatch is melt-spinned to obtain modified polypropylene fibers.
[0012] Furthermore, the conditions for melt spinning are: screw temperature 220-230°C, metering pump specification 0.4-0.6mL / r, metering pump speed 22-25r / min, spinneret hole diameter 0.4-0.6mm, number of holes 17-19, winding speed 230-250m / min, and the filament bundle is subjected to 4-5 times hot drawing after winding.
[0013] Furthermore, the polypropylene comprises polypropylene No. 1, polypropylene No. 2 and polypropylene No. 3 in a weight ratio of 1: (1.3-1.5): (0.6-0.8); the melt index of the polypropylene No. 1 is 28g / 10min under the conditions of 2.16kg and 230°C, and the tensile strength at yield is 180kg / cm 2 , flexural modulus 9000kg / cm 2 ; Model: PP Korea SKBH3820; The melt index of the No. 2 polypropylene is 45g / 10min at 2.16kg and 230℃, and the tensile strength at yield is 300kg / cm 2 , flexural modulus 12000kg / cm 2 ; Model: PP Korea SKR390Y; The melt index of the No. 3 polypropylene is 40g / 10min at 2.16kg and 230℃, and the tensile strength at yield is 270kg / cm 2 , flexural modulus 13000kg / cm 2 ; Model: PP Korea SK B391G. Purchased from Shanghai Langte Import and Export Co., Ltd.
[0014] The present invention attempts to add polypropylene fiber to the system to improve the compressive strength of cement-based composite materials, but the effect is not ideal. The present invention has a good improvement effect on the 28d compressive strength of cement-based composite materials by preparing modified polypropylene fiber. Analysis shows that amphiphilic titanium dioxide is grafted on the modified polypropylene fiber, which makes the modified polypropylene fiber more dispersible in the system and more compatible with other components of the system. A complex network structure can be formed during the hardening process of the cement-based composite material, and the interface transition zone between cement slurry and coarse aggregate in concrete can be enhanced, thereby improving the overall bearing capacity and improving the compressive strength of the cement-based composite material.
[0015] Furthermore, the preparation method of the modified nanomaterial comprises the following steps:
[0016] (1) 10 parts by weight of nanomaterial, 4-4.5 parts by weight of hexadecyltrimethylammonium bromide, 17-20 parts by weight of water and 0.10-0.15 parts by weight of NaCl, adjusting the pH value of the system to 8.0-8.2 with 0.1 mol / L NaOH solution, placing in a ball mill, rotating at 300-350 r / min for 4-5 h, washing, filtering, and vacuum drying to obtain a pre-modified nanomaterial;
[0017] (2) Add 5 parts by weight of the pre-modified nanomaterial to 30-35 parts by weight of 50-55% ethanol aqueous solution, continue to add 0.7-0.9 parts by weight of polyvinyl alcohol, ball mill at 400 r / min for 4-5 hours, wash, filter and dry to obtain the modified nanomaterial.
[0018] Furthermore, the nano material is a mixture of carbon nanotubes, nano silicon dioxide and nano cerium oxide in a weight ratio of 1: (1.2-1.4): (0.5-0.7).
[0019] Furthermore, the carbon nanotubes have a diameter of 1-2 nm, a length of 1-3 μm, and a specific surface area of 420 m 2 / g; the particle size of nano-silicon dioxide is 10-15nm, and the specific surface area is 250m 2 / g; the particle size of nano cerium oxide is 20-30nm, and the specific surface area is 15m 2 / g.
[0020] Since nanomaterials are easy to agglomerate, they do not work well in the system. The present invention can improve the impermeability of cement-based composite materials by modifying the nanomaterials. The modified nanofiller has better dispersibility in the system, can improve its compatibility with the cement matrix, promote better interface bonding, and carbon nanotubes, nano-silicon dioxide and nano-cerium oxide can be filled into the micropores and microscopic defects of concrete, reduce porosity, reduce the possibility of water penetration, and thus improve the density of concrete.
[0021] Furthermore, the water-based epoxy resin emulsion comprises water-based epoxy resin No. 1, water-based epoxy resin No. 2 and water-based epoxy resin No. 3 in a weight ratio of 1: (1.2-1.4): (0.5-0.8); wherein the epoxy equivalent of water-based epoxy resin No. 1 is 183-190 g / eq, and the viscosity is 10000-14000 mPa.s / 25°C; the epoxy equivalent of water-based epoxy resin No. 2 is 175-185 g / eq, and the viscosity is 8000-11000 mPa.s / 25°C; the epoxy equivalent of water-based epoxy resin No. 3 is 320-360 g / eq, and the viscosity is 100-5000 cps / 25°C.
[0022] The present invention can improve the flexural tensile strength of cement-based composite materials by adding water-based epoxy resin. And when using water-based epoxy resin with specific parameters and polypropylene with specific parameters, the freeze-thaw resistance of cement-based composite materials can be improved. Analysis is that water-based epoxy resin can form a continuous film inside concrete, close micropores and cracks, and polypropylene fiber can form a three-dimensional network structure in concrete, effectively inhibiting the development of microcracks, and the two can synergistically reduce the crack expansion caused by freeze-thaw cycles. The sealing effect of epoxy resin with specific parameters and modified polypropylene fiber prepared by polypropylene with specific parameters can provide double protection, and both have better crack inhibition effect, significantly improve the freeze-thaw resistance of concrete, and when concrete shrinks and expands in freeze-thaw cycles, the fiber can bridge the cracks to prevent it from further expansion. At the same time, the slump of cement-based composite materials is improved.
[0023] In order to improve the 2h compressive strength, the quick-hardening agent further comprises the following components in parts by weight: 20-30 parts of calcium sulfoaluminate, 36-43 parts of anhydrous gypsum and 10-15 parts of light-burned magnesium oxide.
[0024] Furthermore, the polyamine curing agent is selected from hydroxyethyldiethylenetriamine or dihydroxyethyldiethylenetriamine.
[0025] Furthermore, the polycarboxylate water-reducing agent is an early-strength polycarboxylate water-reducing agent purchased from Tianjin Feilong Concrete Admixture Co., Ltd., with a water reduction rate of 29% and a water bleeding rate of 15%.
[0026] The present invention also provides a method for preparing a high-strength early-strength cement-based composite material, comprising the following steps: mixing the components uniformly, standing at 65-70° C. for 60-70 minutes, and obtaining a high-strength early-strength cement-based composite material.
[0027] Compared with the prior art, the advantages and beneficial effects of the present invention are:
[0028] 1. The present invention has a good improvement effect on the 28d compressive strength of cement-based composite materials by preparing modified polypropylene fibers.
[0029] 2. The present invention can improve the impermeability of cement-based composite materials by modifying nanomaterials.
[0030] 3. The present invention can improve the flexural tensile strength of cement-based composite materials by adding water-based epoxy resin, and also improve the slump of cement-based composite materials.
[0031] 4. When using waterborne epoxy resin with specific parameters and polypropylene with specific parameters, the freeze-thaw resistance of cement-based composites can be improved. DETAILED DESCRIPTION
[0032] The technical solutions in the embodiments of the present invention are described clearly and completely below. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of them. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.
[0033] The raw materials used in the following examples of the present invention are all commercially available products:
[0034] Hydroxypropyl methylcellulose was purchased from Jinzhou Honghai Cellulose Co., Ltd. The 2% aqueous solution has a viscosity of 42-56 dyn / cm; the viscosity is 200-200000; and the pass rate of 100 mesh is greater than 98.5%.
[0035] Ordinary Portland cement is ordinary Portland cement P.O22.5.
[0036] Silica fume, Gansu Lixinyuan Microsilica Fume Co., Ltd.
[0037] Quartz sand, Dongguan Liaobu Better Abrasive Materials Business Department, specification 100-200 mesh.
[0038] Defoaming agent, Foshan Nanhai Datian Chemical Co., Ltd., model: AS01.
[0039] The particle size of titanium dioxide is 50-70nm and the specific surface area is 20-30m 2 / g.
[0040] The molecular weight of polyvinyl alcohol is 30000-45000 and was purchased from Henan Shoujie Chemical Products Co., Ltd.
[0041] The carbon nanotubes have a diameter of 1-2 nm, a length of 1-3 μm, and a specific surface area of 420 m 2 / g. Purchased from Jiangsu Xianfeng Nanomaterial Technology Co., Ltd.
[0042] The particle size of nano-silicon dioxide is 10-15nm and the specific surface area is 250m 2 / g, purchased from Beijing Dekedao Gold Technology Co., Ltd.
[0043] The particle size of nano cerium oxide is 20-30nm and the specific surface area is 15m 2 / g, purchased from Beijing Dekedao Gold Technology Co., Ltd.
[0044] Example 1
[0045] The present embodiment provides a high-strength and early-strength cement-based composite material, comprising the following components in parts by weight: 420 parts of ordinary Portland cement, 23 parts of silica fume, 10 parts of modified polypropylene fiber, 85 parts of water-based epoxy resin emulsion, 2 parts of modified nanomaterials, 11 parts of polyamine curing agent, 55 parts of quartz sand, 9 parts of hydroxypropyl methylcellulose, 70 parts of quick-hardening agent, 6 parts of water reducer and 2 parts of defoaming agent.
[0046] The quick-hardening agent comprises the following components in parts by weight: 25 parts of calcium sulfoaluminate, 40 parts of anhydrous gypsum and 12 parts of light-burned magnesium oxide.
[0047] The polyamine curing agent is hydroxyethyldiethylenetriamine.
[0048] The water reducing agent is an early strength polycarboxylate water reducing agent purchased from Tianjin Feilong Concrete Admixture Co., Ltd., with a water reduction rate of 29% and a water bleeding rate of 15%.
[0049] The preparation method of modified polypropylene fiber comprises the following steps:
[0050] (1) 90 parts by weight of polypropylene, 6 parts by weight of titanium dioxide, and 5 parts by weight of 3-isocyanate propyltrimethoxysilane were uniformly mixed, and the mixture was mixed and extruded into granules by a twin-screw extruder at an extrusion temperature of 182° C. to obtain a modified polypropylene masterbatch;
[0051] (2) The modified polypropylene masterbatch was melt-spun. The melt spinning conditions were as follows: screw temperature 225°C, metering pump specification 0.5 mL / r, metering pump speed 24 r / min, spinneret hole diameter 0.5 mm, hole number 18, winding speed 240 m / min, and after winding, the filament bundle was subjected to 4 times heat drawing to obtain modified polypropylene fiber.
[0052] The polypropylene comprises No. 1 polypropylene, No. 2 polypropylene and No. 3 polypropylene in a weight ratio of 1:1.4:0.7; the melt index of No. 1 polypropylene is 28g / 10min under the conditions of 2.16kg and 230℃, and the tensile strength at yield is 180kg / cm 2 , flexural modulus 9000kg / cm 2 ; Model: PP Korea SKBH3820; The melt index of the No. 2 polypropylene is 45g / 10min at 2.16kg and 230℃, and the tensile strength at yield is 300kg / cm 2, flexural modulus 12000kg / cm 2 ; Model: PP Korea SKR390Y; The melt index of the No. 3 polypropylene is 40g / 10min at 2.16kg and 230℃, and the tensile strength at yield is 270kg / cm 2 , flexural modulus 13000kg / cm 2 ; Model: PP Korea SK B391G. Purchased from Shanghai Langte Import and Export Co., Ltd.
[0053] The preparation method of the modified nanomaterial comprises the following steps:
[0054] (1) 10 parts by weight of nanomaterial, 4.2 parts by weight of hexadecyltrimethylammonium bromide, 19 parts by weight of water and 0.12 parts by weight of NaCl are placed in a ball mill and milled at a speed of 320 r / min for 4.5 hours to obtain a pre-modified nanomaterial; the nanomaterial is a mixture of carbon nanotubes, nanosilicon dioxide and nanocerium oxide in a weight ratio of 1:1.3:0.6. The carbon nanotubes have a diameter of 1-2 nm, a length of 1-3 μm and a specific surface area of 420 m 2 / g; the particle size of nano-silicon dioxide is 10-15nm, and the specific surface area is 250m 2 / g; the particle size of nano cerium oxide is 20-30nm, and the specific surface area is 15m 2 / g.
[0055] (2) Add 5 parts by weight of the pre-modified nanomaterial to 32 parts by weight of 52% ethanol aqueous solution, continue to add 0.8 parts by weight of polyvinyl alcohol, ball mill at 400 r / min for 4.5 hours, wash, filter and dry to obtain the modified nanomaterial.
[0056] The water-based epoxy resin emulsion includes water-based epoxy resin No. 1, water-based epoxy resin No. 2 and water-based epoxy resin No. 3 in a weight ratio of 1:1.3:0.7; the epoxy equivalent of water-based epoxy resin No. 1 is 183-190 g / eq, and the viscosity is 10000-14000 mPa.s / 25°C; brand: Nantong Xingchen, model: epoxy resin 0164. The epoxy equivalent of water-based epoxy resin No. 2 is 175-185 g / eq, and the viscosity is 8000-11000 mPa.s / 25°C; brand: Nantong Xingchen; model: epoxy resin 0161. The epoxy equivalent of water-based epoxy resin No. 3 is 320-360 g / eq, and the viscosity is 100-5000 cps / 25°C; brand: Jiangsu Kumho, model: KWER834-57.
[0057] The preparation method of the high-strength early-strength cement-based composite material comprises the following steps: mixing the components uniformly, standing at 68° C. for 65 minutes, and obtaining the high-strength early-strength cement-based composite material.
[0058] Example 2
[0059] The present embodiment provides a high-strength and early-strength cement-based composite material, comprising the following components in parts by weight: 400 parts of ordinary Portland cement, 25 parts of silica fume, 7 parts of modified polypropylene fiber, 90 parts of water-based epoxy resin emulsion, 1 part of modified nanomaterial, 12 parts of polyamine curing agent, 530 parts of quartz sand, 12 parts of hydroxypropyl methylcellulose, 60 parts of quick-hardening agent, 7 parts of water reducing agent and 1 part of defoaming agent.
[0060] The quick-hardening agent comprises the following components in parts by weight: 20 parts of calcium sulfoaluminate, 43 parts of anhydrous gypsum and 10 parts of light-burned magnesium oxide.
[0061] The polyamine curing agent is dihydroxyethyl diethylene triamine.
[0062] The water reducing agent is an early strength polycarboxylate water reducing agent purchased from Tianjin Feilong Concrete Admixture Co., Ltd., with a water reduction rate of 29% and a water bleeding rate of 15%.
[0063] The preparation method of modified polypropylene fiber comprises the following steps:
[0064] (1) 90 parts by weight of polypropylene, 7 parts by weight of titanium dioxide, and 4 parts by weight of 3-isocyanate propyltrimethoxysilane were uniformly mixed, and the mixture was mixed and extruded into granules by a twin-screw extruder at an extrusion temperature of 185° C. to obtain a modified polypropylene masterbatch;
[0065] (2) The modified polypropylene masterbatch was melt-spun. The melt spinning conditions were as follows: screw temperature 220°C, metering pump specification 0.6 mL / r, metering pump speed 22 r / min, spinneret hole diameter 0.6 mm, hole number 17, winding speed 250 m / min, and after winding, the filament bundle was heat-stretched 5 times to obtain modified polypropylene fiber.
[0066] The polypropylene comprises No. 1 polypropylene, No. 2 polypropylene and No. 3 polypropylene in a weight ratio of 1:1.3:0.8; the melt index of No. 1 polypropylene is 28g / 10min under the conditions of 2.16kg and 230℃, and the tensile strength at yield is 180kg / cm 2 , flexural modulus 9000kg / cm 2 ; Model: PP Korea SKBH3820; The melt index of the No. 2 polypropylene is 45g / 10min at 2.16kg and 230℃, and the tensile strength at yield is 300kg / cm 2 , flexural modulus 12000kg / cm 2; Model: PP Korea SKR390Y; The melt index of the No. 3 polypropylene is 40g / 10min at 2.16kg and 230℃, and the tensile strength at yield is 270kg / cm 2 , flexural modulus 13000kg / cm 2 ; Model: PP Korea SK B391G. Purchased from Shanghai Langte Import and Export Co., Ltd.
[0067] The preparation method of the modified nanomaterial comprises the following steps:
[0068] (1) 10 parts by weight of nanomaterial, 4 parts by weight of hexadecyltrimethylammonium bromide, 20 parts by weight of water and 0.10 parts by weight of NaCl are added, the pH value of the system is adjusted to 8.2 with 0.1 mol / L NaOH solution, and the mixture is put into a ball mill and milled at a speed of 300 r / min for 5 hours, washed, filtered and vacuum dried to obtain a pre-modified nanomaterial; the nanomaterial is a mixture of carbon nanotubes, nanosilicon dioxide and nanocerium oxide in a weight ratio of 1:1.2:0.7. The carbon nanotubes have a diameter of 1-2 nm, a length of 1-3 μm and a specific surface area of 420 m 2 / g; the particle size of nano-silicon dioxide is 10-15nm, and the specific surface area is 250m 2 / g; the particle size of nano cerium oxide is 20-30nm, and the specific surface area is 15m 2 / g.
[0069] (2) Add 5 parts by weight of the pre-modified nanomaterial to 30 parts by weight of 55% ethanol aqueous solution, add 0.7 parts by weight of polyvinyl alcohol, ball mill at 400 r / min for 5 h, wash, filter and dry to obtain the modified nanomaterial.
[0070] The water-based epoxy resin emulsion includes water-based epoxy resin No. 1, water-based epoxy resin No. 2 and water-based epoxy resin No. 3 in a weight ratio of 1:1.2:0.8; the epoxy equivalent of water-based epoxy resin No. 1 is 183-190 g / eq, and the viscosity is 10000-14000 mPa.s / 25°C; brand: Nantong Xingchen, model: epoxy resin 0164. The epoxy equivalent of water-based epoxy resin No. 2 is 175-185 g / eq, and the viscosity is 8000-11000 mPa.s / 25°C; brand: Nantong Xingchen; model: epoxy resin 0161. The epoxy equivalent of water-based epoxy resin No. 3 is 320-360 g / eq, and the viscosity is 100-5000 cps / 25°C; brand: Jiangsu Kumho, model: KWER834-57.
[0071] The preparation method of the high-strength early-strength cement-based composite material comprises the following steps: mixing the components uniformly, standing at 65° C. for 70 minutes, and obtaining the high-strength early-strength cement-based composite material.
[0072] Comparative Example 1
[0073] The difference between this comparative example and Example 1 is: a high-strength early-strength cement-based composite material, comprising the following components in parts by weight: 420 parts of ordinary Portland cement, 23 parts of silica fume, 15 parts of modified polypropylene fiber, 77 parts of water-based epoxy resin emulsion, 5 parts of modified nanomaterials, 11 parts of polyamine curing agent, 55 parts of quartz sand, 9 parts of hydroxypropyl methylcellulose, 70 parts of quick-hardening agent, 6 parts of water reducer and 2 parts of defoaming agent.
[0074] Comparative Example 2
[0075] The difference between this comparative example and Example 1 is that the polypropylene comprises No. 1 polypropylene, No. 2 polypropylene and No. 3 polypropylene in a weight ratio of 1:1:1; the melt index of No. 1 polypropylene is 28g / 10min under the conditions of 2.16kg and 230℃, and the tensile strength at yield is 180kg / cm 2 , flexural modulus 9000kg / cm 2 ; Model: PP Korea SKBH3820; The melt index of the No. 2 polypropylene is 45g / 10min at 2.16kg and 230℃, and the tensile strength at yield is 300kg / cm 2 , flexural modulus 12000kg / cm 2 ; Model: PP Korea SKR390Y; The melt index of the No. 3 polypropylene is 60g / 10min at 2.16kg and 230℃, and the tensile strength at yield is 180kg / cm 2 , flexural modulus 8500kg / cm 2 ; Model: PP Korea SKBH3820. Purchased from Shanghai Langte Import and Export Co., Ltd.
[0076] Comparative Example 3
[0077] The difference between this comparative example and Example 1 is that the polypropylene comprises No. 1 polypropylene, No. 2 polypropylene and No. 3 polypropylene in a weight ratio of 1:1.4:0.7; the melt index of No. 1 polypropylene is 6.0g / 10min under the conditions of 2.16kg and 230℃, and the tensile strength at yield is 260kg / cm 2 , flexural modulus 10000kg / cm 2 ; Model: PP Korea SK R140M; The melt index of the No. 2 polypropylene is 60g / 10min at 2.16kg and 230℃, and the tensile strength at yield is 180kg / cm 2 , flexural modulus 8500kg / cm 2; Model: PP Korea SK BH3910; The melt index of the No. 3 polypropylene is 60g / 10min at 3.5kg and 230℃, and the tensile strength at yield is 170kg / cm 2 , flexural modulus 12000kg / cm 2 ; Model: PP Korea SK B330F. Purchased from Shanghai Langte Import and Export Co., Ltd.
[0078] Comparative Example 4
[0079] The difference between this comparative example and Example 1 is that the preparation method of the modified nanomaterial comprises the following steps: adding 5 parts by weight of nanomaterial to 32 parts by weight of 52% ethanol aqueous solution, further adding 0.8 parts by weight of polyvinyl alcohol, ball milling at 400 r / min for 4.5 hours, washing, filtering and drying to obtain the modified nanomaterial.
[0080] The nanomaterial is a mixture of carbon nanotubes, nano silicon dioxide and nano cerium oxide in a weight ratio of 1:1.3:0.6. The carbon nanotubes have a diameter of 1-2nm, a length of 1-3μm, and a specific surface area of 420m 2 / g; the particle size of nano-silicon dioxide is 10-15nm, and the specific surface area is 250m 2 / g; the particle size of nano cerium oxide is 20-30nm, and the specific surface area is 15m 2 / g.
[0081] Comparative Example 5
[0082] The difference between this comparative example and Example 1 is that the nano material is a mixture of carbon nanotubes, nano silicon dioxide and nano cerium oxide in a weight ratio of 1:1:1.
[0083] Comparative Example 6
[0084] The difference between this comparative example and Example 1 is that the water-based epoxy resin emulsion comprises water-based epoxy resin No. 1, water-based epoxy resin No. 2 and water-based epoxy resin No. 3 in a weight ratio of 1:1:1; wherein the epoxy equivalent of water-based epoxy resin No. 1 is 183-190 g / eq, and the viscosity is 10000-14000 mPa.s / 25°C; the epoxy equivalent of water-based epoxy resin No. 2 is 175-185 g / eq, and the viscosity is 8000-11000 mPa.s / 25°C; the epoxy equivalent of water-based epoxy resin No. 3 is 320-360 g / eq, and the viscosity is 100-5000 cps / 25°C.
[0085] Comparative Example 7
[0086] The difference between this comparative example and Example 1 is that the water-based epoxy resin emulsion includes water-based epoxy resin No. 1, water-based epoxy resin No. 2 and water-based epoxy resin No. 3 in a weight ratio of 1:1.3:0.7; wherein the epoxy equivalent of water-based epoxy resin No. 1 is 500-600g / eq, and the viscosity at 25°C is 1000-6000mPa·s. Brand: American Hansen Moment, model: Epikote6520-WH-53A. The epoxy equivalent of water-based epoxy resin No. 2 is 195-210, and the viscosity at 25°C is 15000-25000. Brand: American Hansen Moment, model: EpikoteWD-52A. The epoxy equivalent of water-based epoxy resin No. 3 is 191-211g / eq, and the viscosity at 25°C is 1000-7000mPa·s. Brand: Shanghai Kaiyin Chemical Co., Ltd., Model: Water-based epoxy resin KWER834-57.
[0087] Performance Testing
[0088] The cement-based composite materials prepared in Examples 1-2 and Comparative Examples 1-7 were used as samples for performance testing:
[0089] Refer to GB / T50080-2016 to determine the slump;
[0090] Referring to GB / T50081-2019, the cement-based composite materials were cured at a curing temperature of 25±2°C and a relative humidity of 90±5%. The compressive strength at each age was measured, and the tensile and flexural strength and freeze-thaw resistance were tested after 28 days of curing.
[0091] Impermeability: Refer to GB / T50082-2009 to measure the maximum hydrostatic pressure of the sample without water seepage.
[0092] The results are shown in Table 1.
[0093] Table 1 Performance test results
[0094]
[0095]
[0096] It can be seen from the above performance test results that the comprehensive performance of Examples 1-2 is excellent, especially the comprehensive performance of Example 1 is the most outstanding, which is mainly due to the synergistic compounding of multiple components.
[0097] The comparative examples, however, are significantly inferior to the embodiments in the corresponding performance tests because they do not adopt the necessary technical solutions. In comparative example 1, the ratios of modified polypropylene fiber, water-based epoxy resin emulsion, and modified nanomaterials are changed. It can be found that the performance of the samples has decreased to varying degrees, indicating that the three components work synergistically in the system to synergistically improve the performance of the composite material. The ratio of polypropylene in comparative example 2 is different, and the 28d compressive strength of the cement-based composite material decreases; the parameters of polypropylene in comparative example 3 are different, and it can be seen from the results that the freeze-thaw resistance effect decreases. The preparation method of the modified nanomaterial in comparative example 4 is different, and the impermeability decreases. The analysis is that the nanomaterial is not pretreated, the reaction with polyvinyl alcohol is uneven, and the coating effect is not good. The composition of the nanomaterial in comparative example 5 is different, and the impermeability decreases, indicating that the three nanomaterials work synergistically with each other. The ratio of water-based epoxy resin in comparative example 6 is different, and the flexural tensile strength of the cement-based composite material decreases, and the slump decreases. The parameters of water-based epoxy resin in comparative example 7 are different, and the freeze-thaw resistance of the cement-based composite material decreases. The above experimental results further prove the importance of the technical solution defined in the present invention to its technical effect.
[0098] The above is a preferred embodiment of the present invention. It should be pointed out that for ordinary technicians in this technical field, several improvements and modifications can be made without departing from the principles of the present invention. These improvements and modifications should also be regarded as the scope of protection of the present invention.
Claims
1. A high-strength early-strength cement-based composite material, characterized in that: The invention comprises the following components in parts by weight: 400-450 parts of ordinary Portland cement, 20-25 parts of silica fume, 7-12 parts of modified polypropylene fiber, 80-90 parts of waterborne epoxy resin emulsion, 1-3 parts of modified nanomaterials, 10-12 parts of polyamine curing agent, 530-580 parts of quartz sand, 5-12 parts of hydroxypropyl methylcellulose, 60-80 parts of quick-hardening agent, 4-7 parts of water reducing agent and 1-3 parts of defoaming agent; The preparation method of modified polypropylene fiber comprises the following steps: (1) 90 parts by weight of polypropylene, 5-7 parts by weight of titanium dioxide, and 4-6 parts by weight of 3-isocyanate propyltrimethoxysilane are uniformly mixed, and the mixture is mixed and extruded into granules by a twin-screw extruder at an extrusion temperature of 180-185° C. to obtain a modified polypropylene masterbatch; (2) The modified polypropylene masterbatch is melt-spinned to obtain modified polypropylene fibers.
2. The high-strength early-strength cement-based composite material according to claim 1, characterized in that: The conditions for melt spinning are: screw temperature 220-230°C, metering pump specification 0.4-0.6mL / r, metering pump speed 22-25r / min, spinneret hole diameter 0.4-0.6mm, number of holes 17-19, winding speed 230-250m / min, and the filament bundle is subjected to 4-5 times hot drawing after winding.
3. The high-strength early-strength cement-based composite material according to claim 1, characterized in that: The preparation method of the modified nanomaterial comprises the following steps: (1) 10 parts by weight of nanomaterial, 4-4.5 parts by weight of hexadecyltrimethylammonium bromide, 17-20 parts by weight of water and 0.10-0.15 parts by weight of NaCl, adjusting the pH value of the system to 8.0-8.2, placing in a ball mill, rotating at 300-350 r / min for 4-5 hours, washing, filtering, and vacuum drying to obtain a pre-modified nanomaterial; (2) Add 5 parts by weight of the pre-modified nanomaterial to 30-35 parts by weight of ethanol aqueous solution, continue to add 0.7-0.9 parts by weight of polyvinyl alcohol, ball mill for 4-5 hours, wash, filter and dry to obtain the modified nanomaterial.
4. The high-strength early-strength cement-based composite material according to claim 3, characterized in that: The nano material is a mixture of carbon nano tubes, nano silicon dioxide and nano cerium oxide in a weight ratio of 1: (1.2-1.4): (0.5-0.7).
5. The high-strength early-strength cement-based composite material according to claim 3, characterized in that: The mass percentage of ethanol in the ethanol aqueous solution is 50-55%.
6. The high-strength early-strength cement-based composite material according to claim 4, characterized in that: The carbon nanotubes have a diameter of 1-2 nm, a length of 1-3 μm, and a specific surface area of 420 m 2 / g; the particle size of nano-silicon dioxide is 10-15nm, and the specific surface area is 250m 2 / g; the particle size of nano cerium oxide is 20-30nm, and the specific surface area is 15m 2 / g.
7. The high-strength early-strength cement-based composite material according to claim 1, characterized in that: The water-based epoxy resin emulsion comprises water-based epoxy resin No. 1, water-based epoxy resin No. 2 and water-based epoxy resin No. 3 in a weight ratio of 1: (1.2-1.4): (0.5-0.8); the epoxy equivalent of water-based epoxy resin No. 1 is 183-190 g / eq, and the viscosity is 10000-14000 mPa.s / 25°C; the epoxy equivalent of water-based epoxy resin No. 2 is 175-185 g / eq, and the viscosity is 8000-11000 mPa.s / 25°C; the epoxy equivalent of water-based epoxy resin No. 3 is 320-360 g / eq, and the viscosity is 100-5000 cps / 25°C.
8. The high-strength early-strength cement-based composite material according to claim 7, characterized in that: The quick-hardening agent comprises the following components in parts by weight: 20-30 parts of calcium sulfoaluminate, 36-43 parts of anhydrous gypsum and 10-15 parts of light-burned magnesium oxide.
9. The high-strength early-strength cement-based composite material according to claim 1, characterized in that: The polyamine curing agent is selected from hydroxyethyldiethylenetriamine or dihydroxyethyldiethylenetriamine.
10. A method for preparing the high-strength early-strength cement-based composite material according to any one of claims 1 to 9, characterized in that: The method comprises the following steps: mixing the components uniformly, standing at 65-70° C. for 60-70 minutes, and obtaining a high-strength early-strength cement-based composite material.
Citation Information
Patent Citations
Aqueous epoxy-modified cement mortar
CN103951352A
Anti-freezing concrete mixture and preparation method thereof
CN112408911A
Marine concrete corrosion inhibitor and preparation method thereof
CN114477839A